Management Science Education: Nature and Nurture - Howard, Ronald A. (Management Science, 1970)
I have earlier commented on the need for practicality in management science education. Here I would like to emphasize the form of the educational program and the personal characteristics of those who complete it successfully. The crucial problem in education would seem to be the development of individuals who have the intellectual curiosity and competence of our best research students and yet retain the pragmatism, perception, and judgment of our best practitioners. I believe that one answer to this problem is a Ph.D. level professional program that combines a unified view of theory with the opportunity to test the theory in practice. I believe further that the key to integration is the utilization of a new language for decision processes founded on decision theory and systems analysis—the language of decision analysis.